2016
DOI: 10.1016/j.physa.2016.06.111
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of the global container shipping network to targeted link disruption

Abstract: Using complex network theory to describe the relational geography of maritime networks has provided great insights regarding their hierarchy and evolution over the past two decades. Unlike applications in other transport fields, notably air transport, complex network theory has had limited application in studying the vulnerability of maritime networks. This study uses targeted link disruption to investigate the strategy specific vulnerability of the network. Although nodal infrastructure such as ports can rend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 53 publications
1
47
0
Order By: Relevance
“…Further studies will consider the ability of each port for tropical cyclone prevention, such as the number of shelters and protection structures. Moreover, if possible, further studies will use automatic identification system (AIS) data to construct a more intact maritime network in the Northwest Pacific and the northern Indian Ocean [34]. Finally, some particular ports may have necessary coordination and ship re-routing plans after port disruption occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will consider the ability of each port for tropical cyclone prevention, such as the number of shelters and protection structures. Moreover, if possible, further studies will use automatic identification system (AIS) data to construct a more intact maritime network in the Northwest Pacific and the northern Indian Ocean [34]. Finally, some particular ports may have necessary coordination and ship re-routing plans after port disruption occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of complex network theory is permeating into many different fields [39][40][41][42][43][44]. Some studies have shown that complex network theory can be used to quantitatively and qualitatively reflect various real network systems and reveal the complicated characteristics of the network [45].…”
Section: Complex Network Analysis Methodsmentioning
confidence: 99%
“…Some studies have shown that complex network theory can be used to quantitatively and qualitatively reflect various real network systems and reveal the complicated characteristics of the network [45]. If a port is regarded as a node and there is any ship between two ports, the line between the two ports is regarded as an edge [39].…”
Section: Complex Network Analysis Methodsmentioning
confidence: 99%
“…Single layer studies on transportation systems are extensive covering air transport (Lordan et al, 2016(Lordan et al, , 2015Lordan, 2014;Lordan et al, 2014b;Sun et al, 2017;Zanin et al, 2009;Zanin and Lillo, 2013), maritime networks (Bartholdi and Jarumaneeroj, 2014;Ducruet et al, 2010a,b;Ducruet and Notteboom, 2012;Ducruet, 2016;González Laxe et al, 2012;Hu and Zhu, 2009;Fraser et al, 2014;Mohamed-Chérif and Ducruet, 2016;Pais Montes et al, 2012;Tsiostas and Polyzos, 2015;Viljoen and Joubert, 2016), train, bus, tram and subway systems (Criado et al, 2007;Kurant and Thiran, 2006a;Mouronte and Benito, 2012;Ouyang et al, 2014;Sen et al, 2003), and the structural properties and vulnerability of road networks (Crucitti et al, 2006;Duan and Lu, 2014;Gudmundsson and Mohajeri, 2013;Háznagy et al, 2015;Jiang, 2007;Jiang and Claramunt, 2004;Porta et al, 2012;Reggiani et al, 2011;Rupi et al, 2015;Strano et al, 2009;Zadeh and Rajabi, 2013).…”
Section: Transportation Applicationsmentioning
confidence: 99%
“…Flexibility refers to the network's inherent ability to find alternative paths if the shortest paths are destroyed. Measuring flexibility is slightly more tricky, but most typically authors have used the clustering coefficient, arguing that well-connected neighbourhoods offer more rerouting options (Thadakamalla et al, 2004;Viljoen and Joubert, 2016).…”
Section: Vulnerability Of Multilayered Networkmentioning
confidence: 99%